2011
DOI: 10.3324/haematol.2011.046888
|View full text |Cite
|
Sign up to set email alerts
|

Integrative nucleophosmin mutation-associated microRNA and gene expression pattern analysis identifies novel microRNA - target gene interactions in acute myeloid leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundMicroRNAs are regulators of gene expression, which act mainly by decreasing mRNA levels of their multiple targets. Deregulated microRNA expression has been shown for acute myeloid leukemia, a disease also characterized by altered gene expression associated with distinct genomic aberrations such as nucleophosmin (NPM1) mutations. To shed further light on the role of deregulated microRNA and gene expression in cytogenetically normal acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…(17,18) miR-30c can also trigger upregulation of transmembrane tumor necrosis factor-a expression and enhance NK cell cytotoxicity against hepatoma cell lines.…”
mentioning
confidence: 99%
“…(17,18) miR-30c can also trigger upregulation of transmembrane tumor necrosis factor-a expression and enhance NK cell cytotoxicity against hepatoma cell lines.…”
mentioning
confidence: 99%
“…NPM1-mutated AML has been found to have a distinctive miRNA expression profile, [17][18][19] however, whether NPM1 is subjected to miRNA regulation is unclear. In this study, we demonstrated that a polymorphic delT in the NPM1 3'-UTR generated an illegitimate binding site for miR-337-5p.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that miR-30c is a key mediator of tumor suppressor function of C/EBPa in AML; likewise, other studies in breast cancer and AML with NPM1 mutations showed a tumor suppressor-like function of miR-30c. 19,20 An in vivo investigation of the whole-mouse bone marrow cells showed an increased expression of miR-30c in granulocytes ( Figure 3A). A disruption of the C/EBPa gene in adult mice selectively blocks granulocytic development.…”
Section: Discussionmentioning
confidence: 99%
“…18 In breast cancer and AML with NPM1 mutations, miR-30c functions like a tumor suppressor. 19,20 There has been no report that shows any specific function of miR-30c in granulopoiesis and AML independent of NPM1 mutations.…”
Section: Introductionmentioning
confidence: 99%